Survey Compliance and the Distribution of Income - Mistiaen, Johan A.; Ravallion, Martin (World Bank, Washington, DC, 2014)
While it is improbable that households with different incomes are equally likely to participate in sample surveys, the lack of data for nonrespondents has hindered efforts to correct for the bias in measures of poverty and inequality. The authors demonstrate how the latent income effect on survey compliance can be estimated using readily available data on response rates across geographic areas. An application using the Current Population Survey for the United States indicates that compliance falls as income rises. Correcting for selective compliance appreciably increases mean income and inequality, but has only a small impact on poverty incidence up to commonly used poverty lines in the United States.